THE IKIGAI SCALE ON NGUYEN TAT THANH UNIVERSITY STUDENTS: VALIDITY ASSESSMENT - Vo Bich, Tuyen; Pham Nguyen Trong, Nhan (TẠP CHÍ KHOA HỌC TRƯỜNG ĐẠI HỌC TRÀ VINH, 2022)
Originating from Japan, the concept of ‘ikigai’ refers to a ‘reason for living’, a ‘reason for being’ or a ‘reason for waking up in the morning’. Ikigai is a combination of four elements: what you love, what you are good at, what the world needs, and what you can be paid for. Even though Ikigai has made its first steps into the Vietnamese culture through written media, the concept and its associations with mental health aspects in Vietnamese society have not yet been studied. Therefore, this study aimed to assess the validity of the Ikigai-9 scale and its relationships the with mental health aspects of students at a private university in Ho Chi Minh City. A total of 2933 students participated in the research survey to self-report levels of Ikigai, well-being, self-efficacy, stress, depression, and anxiety. The findings indicated that Ikigai has a positive association with well-being and selfefficacy, and a negative association with depression, anxiety, and stress. Therefore, the study is of significance to higher education authorities to introduce new policies to improve students’ mental health.